Advances in inflammatory bowel diseases 2012. (April 2013) - Saad, Abdo M; Kahn, Stacy A; Rubin, Michele; Rubin, David T
The Crohn's and Colitis Foundation of America's (CCFA) Conference, Advances in Inflammatory Bowel Diseases 2012, held in Hollywood (FL, USA), was co-chaired by Richard P MacDermott, from Albany Medical College (NY, USA) and Stephen B Hanauer, from the University of Chicago Medicine (IL, USA). This year's conference saw a record 1947 total registrants and 1862 in attendance. In addition to the scientific meeting, there were committee meetings for the CCFA and several new events this year, including a 'meet the experts' breakfast series, a well-attended fellows workshop and a Scrub Run 5k, which brought in more than 100 runners and was a great way to promote the CCFA's Team Challenge. Highlights of this year's conference included presentations on the etiopathogenesis of inflammatory bowel disease (IBD), new approaches to management, as well as new therapies in the pipeline. With clinical, nursing, pediatric and basic science tracks, the sessions included a diverse range of topics and debates that focused on advancing care for individuals with IBD. In addition, there was an emphasis on balancing the risk of adverse events associated with given therapies and optimizing response. The goal of achieving deep remission as a clinical and research end point continues to be debated. Despite the ongoing progress in R&D of new therapies in IBD, there was a call for larger randomized controlled trials that are necessary for comparative effectiveness research. Awards were also granted for the best poster presentations in the conference.